1955
DOI: 10.2739/kurumemedj.2.128
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization in Igneous Rocks

Abstract: In the course of the investigation of concrements formation in human bodies, which come from body fluid, the author has been making efforts to clear whether any similarity exists between the concrements formation and the crystllization of rock forming minerals, which comes from solution, or not. And the results about the crystallization in igneous rocks, so far obtained, are as follows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1956
1956
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Pederin is a toxin containing two tetrahydropyran cores that causes dermatitis . Pederin was first reported from the beetle Paederus fuscipes and widely believed to be produced by eukaryotes. , However, the discovery of the pederin biosynthetic gene cluster demonstrated that bacterial symbionts of insects, marine invertebrates, and lichens are the true producers of these compounds . Biosynthesis of pederin and its homologues is accomplished by hybrid polyketide/nonribosomal peptide synthases (PKS/NRPS) employing an unusual trans -acyltransferase (AT) PKS mechanism, in which the PKS enzymatic modules utilize a common AT encoded in a separate gene.…”
mentioning
confidence: 99%
“…Pederin is a toxin containing two tetrahydropyran cores that causes dermatitis . Pederin was first reported from the beetle Paederus fuscipes and widely believed to be produced by eukaryotes. , However, the discovery of the pederin biosynthetic gene cluster demonstrated that bacterial symbionts of insects, marine invertebrates, and lichens are the true producers of these compounds . Biosynthesis of pederin and its homologues is accomplished by hybrid polyketide/nonribosomal peptide synthases (PKS/NRPS) employing an unusual trans -acyltransferase (AT) PKS mechanism, in which the PKS enzymatic modules utilize a common AT encoded in a separate gene.…”
mentioning
confidence: 99%